2020
DOI: 10.1101/2020.04.29.068254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Antimicrobial Resistance Using Conserved Genes

Abstract: Abbreviations AIartificial intelligence CI confidence interval ME major error, susceptible genomes predicted to be resistant MIC minimum inhibitory concentration PATRIC Pathosystems resource integration center PLF PATRIC local protein family RAST Rapid annotation using subsystem technology RF Random Forest SR susceptible and resistant VME very major error, resistant genomes predicted to be susceptible XGB XGBoost Abstract A growing number of studies have shown that machine learning algorithms can be used to ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…Together, these findings provide additional evidence that a broad genetic fingerprint, rather than individual virulence or antivirulence factors, is being used to classify strains as having high or low virulence. Furthermore, it is consistent with a recent finding that antimicrobial resistance in several species can be accurately predicted by only considering variation in a small subset of core genes (and excluding known resistance genes) (35).…”
Section: Resultssupporting
confidence: 90%
“…Together, these findings provide additional evidence that a broad genetic fingerprint, rather than individual virulence or antivirulence factors, is being used to classify strains as having high or low virulence. Furthermore, it is consistent with a recent finding that antimicrobial resistance in several species can be accurately predicted by only considering variation in a small subset of core genes (and excluding known resistance genes) (35).…”
Section: Resultssupporting
confidence: 90%
“…When the Salmonella models are recomputed using the chromosome of Salmonella enterica serovar Typhi CT18 as the reference, we also observe nearly identical results (see Table S1D in the supplemental material), indicating that the choice of the reference chromosomes has little impact. Overall, these AUCs and corresponding model statistics, including F1 scores and error rates (see Tables S1E to S1G in the supplemental material), are consistent with previous studies that have used k-mers and AMR genes as input (14,15,26).…”
Section: Resultssupporting
confidence: 87%
“…Since the machine learning models learn from nucleotide similarity that has been observed across samples in the training set, some of the high accuracies are likely due to similar sequences occurring in both the training and testing sets, which may obscure the more broadly conserved nucleotide signatures relating to, or correlating with, resistance. This has been observed previously, and several studies have tried to balance strains based on phylogeny to reduce this effect in the ML models (10,11,21,26). In essence, having related genomes in the training and testing sets can improve accuracies, but may also potentially reduce the generalizability of the models if the overall phylogenetic distribution of the training set is biased.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Strategies for predicting AMR phenotypes in polymicrobial samples present an interesting challenge 36 . We tested the binning approach for the prediction of ARGs in S. aureus and we found that it gives similar results as prediction of ARGs in monomicrobial samples for most of the genes with exception of the blaZ gene.…”
Section: Discussionmentioning
confidence: 99%